THE EFFECT OF USING BOARD GAME IN TEACHING SPEAKING AT THE TENTH GRADE STUDENTS OF SMK SWASTA YPIS MAJU BINJAI - Rizki alfiansyah maulana; AYU INDARI (Jurnal Serunai Bahasa Inggris, 2022)
The aim of this study is to describe whether or not using Board Game is effective in Teaching Speaking at The Tenth Grade Students of SMK Swasta Ypis Maju Binjai. The researchers use Board Game in teaching speaking at the Tenth Grade Students of SMK Swasta Ypis Maju Binjai. This is a pre-experimental research with one group pre-test and post-test design. In this research, the researchers take 25 at the Tenth Grade Students of SMK Swasta Ypis Maju Binjai as the sample among 73 students for its population. Then the researchers give pre-test and post-test by employing instruments that is oral test. The test is to measure the students speaking skill. The result of the research is the highest score of pretest is 84 and the lowest is 58. The highest score of posttest is 88 and the lowest is 72. The mean score of pre-test is 71.04. The mean score of post-test is 80.72. The result of t-test is higher than critical value. The score of t-test is -6.273 and the score of t-table is 2.010, it means that t-test is higher than t-table (-6.273 < 2.010). The score of t-test is 2.010 and the degree of freedom (df) was 24. For 5 % significance level and 24 degree of freedom, the critical value on T table is – 6.273. So, it can be said that Ha is accepted and Ho is rejected. To sum up, the hypothesis is accepted. It means that there is effective of using board game in teaching speaking at the Tenth Grade Students of SMK Swasta Ypis Maju Binjai.